Professionalism and Effectiveness of Internal Audit in Fraud Control: A Qualitative Study of a Construction Company in Indonesia - Egi Satria Nugraha; Fidiana (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study is grounded in the gap that fraud control in construction companies has not yet been comprehensively explained through qualitative evidence on how internal auditors maintain professionalism and audit effectiveness while facing organisational pressures. Accordingly, this study aims to examine the professionalism and effectiveness of internal audit in fraud control within a large Indonesian construction company, with particular attention to the structural, social, and psychological pressures encountered by internal auditors. The study is conceptually situated within internal audit professionalism and corporate governance perspectives, which emphasize integrity, objectivity, independence, and accountability in strengthening organisational control. A qualitative case study approach was employed, using thematic analysis based on Braun and Clarke (2006). Data were collected through semi-structured in-depth interviews with two purposively selected internal auditors, designated as DA and IR, from the Internal Audit Unit of the case company. The interview data were supported by document review of audit reports, work guidelines, and supervisory evaluation records. Trustworthiness was ensured through member checking, document triangulation, and peer debriefing. The findings reveal three main themes. First, internal auditors demonstrated professionalism under pressure by maintaining integrity, objectivity, and independence despite structural and social pressures from management, including implicit directives to modify audit findings. Second, internal audit was implemented systematically through the stages of desk audit, field audit, reporting, and follow-up, supported by a risk-based Annual Supervisory Work Programme (PKPT). Third, the effectiveness of internal audit was constrained by structural and institutional factors, particularly the direct reporting line of the Internal Audit Unit to the president director and selective follow-up compliance by operational units. Theoretically, these findings strengthen the understanding of internal audit professionalism and governance effectiveness in the context of construction companies in emerging markets. Practically, the study highlights the need to strengthen internal audit independence, improve audit committee oversight, and enhance auditor training in managing organisational pressure. Future studies are recommended to involve a broader range of participants, compare multiple construction companies, and incorporate perspectives from audit committees and operational management to develop a more comprehensive understanding of fraud control mechanisms